Analysis of internal audit functioning in Poland – empirical research findings - Bielińska-Dusza, Edita (Business, Management and Economics Engineering, 2011)
The purpose of the article was to present the research conducted in companies, concerning the functioning of internal audit in Poland. During the research, the author identified a number of barriers reducing the efficiency of the cells of internal audit and audit as an instrument for company improvement. One also indicated areas which, from the point of view of internal audit efficiency as well as of the company functioning, should be improved.